Electric efficiency indicators and carbon dioxide emission factors for power generation by fossil and renewable energy sources on hourly basis. (15th September 2019) - Marrasso, E.; Roselli, C.; Sasso, M.
Highlights: Hourly analysis of the Italian electricity production mix is performed. Evaluation of the electricity produced by each fossil and renewable source with a hourly time resolution. Four power plant efficiency indicators are defined and evaluated. Three equivalent carbon dioxide emission factors are determined. Abstract: The power system has faced unprecedented challenges in the last decade caused by many factors: the introduction of the open electricity market, the diffusion of distributed generation, the growth of the electricity production from the no-programmable renewable energy sources, etc. In this framework the power generation system turned extremely varied and complex. In addition, European Union highlighted the need to increase the energy efficiency to achieve the goal of 30% savings in primary energy consumption by 2030 compared to 1990 levels. Since the goal is defined on primary energy level, the electric efficiency indicators are central issues in the assessment of energy saving measures that affect electricity demand and involve different processes. However, all European Directives set electric efficiency indicators and carbon dioxide emission factors to fixed values neglecting their intrinsic time-variability due to the primary energy source mix used in the electricity generation hour by hour. The use of a fixed value for these parameters could lead to inaccurate or wrong results in various processes. Indeed, they have an impact on the choice of electricity versus fossil-fuel based technologies. In particular, they affect both the possibility for a product to retain access to European market, and its specific rating in an energy labelling class. Moreover, in the case of the modelling of any energy system that interacts with the power grid the electric efficiency indicators are the crucial factors to assess the potential primary energy savings of the technologies. On another level, the use of an incorrect value of energy and environmental indicators in the evaluation of the primary energy savings of those energy efficiency measures supported by economic mechanisms (as white certificates, policy mechanisms supporting renewables, tax deductions), could lead to an underestimation or an overestimation of the economic support. In this context, the aim of this paper is to perform an hourly analysis of the Italian electricity production mix evaluating the contribution of each primary energy source. The novelty of this approach is related to the evaluation of the electricity produced by each fossil and renewable source with an hourly time resolution over the years 2016 and 2017. Four power plant efficiency indicators and three carbon dioxide emission factors have been also defined and determined on hourly basis for both considered years. The results of the analysis have showed the strongly variability of the considered parameters across the years, the seasons and hour by hour depending upon the hourly power generation mix.